A Bibliometric and Visualized Analysis of the Global Literature on Black Soil Conservation from 1983–2022 Based on CiteSpace and VOSviewer - Yuxuan Xu; Jie Lyu; Hongbin Liu; Ying Xue (Agronomy, 2022)
Many scholars have conducted in-depth studies on the research area of black soil conservation (BSC) and produced fruitful research results, but there is still a lack of scientific quantitative analysis and objective comprehensive evaluation of the research results. In order to grasp and clarify the current status of BSC research, we explored the trending topics and frontier issues in this research field, as well as the overall evolution trend from 1983 to 2022. Based on the publication information of BSC topics in the core database of Web of Science (WOS), this study utilized the superior tools in two major bibliometric software; they are the VOSviewer and CiteSpace to draw visual maps, such as collaboration networks and keyword co-occurrence maps, to further analyze the research progress and frontiers. The results are as follows: First, research on BSC began in 1983 and can be divided into three phases: the period of nascent research, steady development, and rapid growth. The subject increasingly became an area of research focus in academia, but gradually produced signs of intersection with other disciplines, such as agronomy, biology, and economics. Second, the distribution of research institutions and countries has become more concentrated, forming geographically small research clusters in typical black soil area countries, such as Russia and China, where the centrality of research institutions is higher than 0.20. Research networks have also been initially established between developed and developing countries, such as the United States and China, with a high centrality close to 0.50. Third, the research content is increasingly cross-cutting and systematic, and the research focus can be divided into five major areas, such as black soil distribution and physical and chemical characteristics. Fourth, the research areas cover agronomy, chemistry, geography and other levels, and a more systematic research system has been formed. In the future, it is still necessary to strengthen the establishment of data monitoring systems in black soil areas, the improvement of black soil information database, the assertion of conservation tillage technology and the strengthening of extreme climate early warning network to maintain the soil nutrient content and to guarantee the sustainable development of agriculture.